Improving farmers access to agricultural extension services delivery systems: Lessons from a field study in western Uttar Pradesh, India - Nagar, Ankit; Nauriyal, Dinesh Kumar; Singh, Sukhpal (Journal of Tropical Agriculture, 2022)
This paper examines the key determinants of farmers access to agricultural extension services, and the sources of agricultural extension services preferred and accessed by farmers. An ordered logistic regression model was used to analyse the data of 360 sample households based on a primary survey conducted in western Uttar Pradesh, India. The study finds that farmers decision to engage in the agricultural extension programme is significantly influenced by factors such as education level, gender, farming experience, social group, group membership, farm size, credit access, awareness of the extension scheme, farmers perception and distance from extension sources. The most intriguing finding of this study is that progressive farmers, who have long been regarded as a major source of knowledge diffusion, are the most distrusted sources of information as they are suspected of withholding vital information from potential beneficiaries. The positive relationship between farm size and ‘Access’ underlines that the extension services should revisit their strategies for targeting more marginal and small farmers by incorporating their priorities into their outreach programs. The study suggests that marginal and small farmers productive potential could still be greatly augmented by the appropriate technology, advisory services, guidance and improved market access.